2000
DOI: 10.1042/0264-6021:3460537
|View full text |Cite
|
Sign up to set email alerts
|

Rapid replenishment of sphingomyelin in the plasma membrane upon degradation by sphingomyelinase in NIH3T3 cells overexpressing the phosphatidylinositol transfer protein β

Abstract: In order to study the in vivo function of the phosphatidylinositol transfer protein beta (PI-TPbeta), mouse NIH3T3 fibroblasts were transfected with cDNA encoding mouse PI-TPbeta. Two stable cell lines were isolated (SPIbeta2 and SPIbeta8) in which the levels of PI-TPbeta were increased 16- and 11-fold respectively. The doubling time of the SPIbeta cells was about 1.7 times that of the wild-type (wt) cells. Because PI-TPbeta expresses transfer activity towards sphingomyelin (SM) in vitro, the SM metabolism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…The intracellular concentration of PI-TPb is about a 100-fold lower than the concentration of PI-TPa in most mammalian tissues (36). It was shown that PI-TPb is involved in the traffic of SM from the Golgi membranes to the plasma membrane (40). In contrast to the effect of PI-TPa, increased expression of PI-TPb leads to an increase in cell cycle duration from 21 h to 34 h. The saturation density of confluent cultures decreased and the cells were much more sensitive to UV-and TNFa-induced apoptosis when compared to wtNIH3T3 cells (36).…”
Section: Manipulation Of the Expression Of Pi-tpa And Pi-tpbmentioning
confidence: 99%
See 2 more Smart Citations
“…The intracellular concentration of PI-TPb is about a 100-fold lower than the concentration of PI-TPa in most mammalian tissues (36). It was shown that PI-TPb is involved in the traffic of SM from the Golgi membranes to the plasma membrane (40). In contrast to the effect of PI-TPa, increased expression of PI-TPb leads to an increase in cell cycle duration from 21 h to 34 h. The saturation density of confluent cultures decreased and the cells were much more sensitive to UV-and TNFa-induced apoptosis when compared to wtNIH3T3 cells (36).…”
Section: Manipulation Of the Expression Of Pi-tpa And Pi-tpbmentioning
confidence: 99%
“…Involvement of PI-TPa and PI-TPb in the regulation of PC synthesis and/or SM transfer (8,33,40), was not confirmed in COS-7 cells that were transiently transfected with either PI-TPa or PI-TPb (13). An explanation for this discrepancy might be that the effects are strongly dependent on the cell type used for transfection or that transiently transfected cell cultures demonstrate different properties when compared to stable cell lines in particular when autocrine as well as paracrine stimulation processes are involved.…”
Section: Manipulation Of the Expression Of Pi-tpa And Pi-tpbmentioning
confidence: 99%
See 1 more Smart Citation
“…Two separate studies have examined the e¡ects of over-expression of PITPL (which localises at the Golgi) on sphingolipid metabolism. In a study using NIH 3T3 ¢broblasts, hydrolysis of SM at the external lea£et of the plasma membrane by exogenous SMase, led to enhanced replenishment of SM at the plasma membrane [48]. In a second study using COS-7 cells, no changes in replenishment was observed [33].…”
Section: Mechanism Of Lipid Exchangementioning
confidence: 99%
“…In previous studies on wtNIH3T3 cells that have a 10-fold increase in PI-TPβ levels (SPIβ cells) we observed that these cells display a decreased growth rate relative to the wtNIH3T3 cells [7]. In addition, under conditions where sphingomyelin (SM) in the plasma membrane was hydrolyzed to ceramide by exogenous sphingomyelinase, SPIβ cells in contrast to wtNIH3T3 cells maintained the steady-state levels of SM in the plasma membrane suggesting that PI-TPβ was involved in this process [7]. This is in agreement with the finding that in vitro PI-TPβ binds and transfers SM in addition to PI and PC while PI-TPα lacks the ability to transfer SM [8].…”
Section: Introductionmentioning
confidence: 77%